Bioactive lipids in gintonin-enriched fraction from ginseng - Cho, Hee-Jung; Choi, Sun-Hye; Kim, Hyeon-Joong; Lee, Byung-Hwan; Rhim, Hyewon; Kim, Hyoung-Chun; Hwang, Sung-Hee; Nah, Seung-Yeol (Journal of ginseng research, 2019)
Ginseng is a traditional herbal medicine for human health. Ginseng contains a bioactive ligand named gintonin. The active ingredient of gintonin is lysophosphatidic acid C18:2 (LPA C18:2). We previously developed a method for gintonin-enriched fraction (GEF) preparation to mass-produce gintonin from ginseng. However, previous studies did not show the presence of other bioactive lipids besides LPAs. The aim of this study was to quantify the fatty acids, lysophospholipids (LPLs), and phospholipids (PLs) besides LPAs in GEF. We prepared GEF from white ginseng. We used gas chromatography-mass spectrometry for fatty acid analysis and liquid chromatography-tandem mass spectrometry for PL analysis, and quantified the fatty acids, LPLs, and PLs in GEF using respective standards. We examined the effect of GEF on insulin secretion in INS-1 cells. GEF contains about 7.5% linoleic (C18:2), 2.8% palmitic (C16:0), and 1.5% oleic acids (C18:1). GEF contains about 0.2% LPA C18:2, 0.06% LPA C16:0, and 0.02% LPA C18:1. GEF contains 0.08% lysophosphatidylcholine, 0.03% lysophosphatidylethanolamine, and 0.13% lysophosphatidylinositols. GEF also contains about 1% phosphatidic acid (PA) 16:0-18:2, 0.5% PA 18:2-18:2, and 0.2% PA 16:0-18:1. GEF-mediated insulin secretion was not blocked by LPA receptor antagonist. We determined four characteristics of GEF through lipid analysis and insulin secretion. First, GEF contains a large amount of linoleic acid (C18:2), PA 16:0-18:2, and LPA C18:2 compared with other lipids. Second, the main fatty acid component of LPLs and PLs is linoleic acid (C18:2). Third, GEF stimulates insulin secretion not through LPA receptors. Finally, GEF contains bioactive lipids besides LPAs.